Plasmonic properties of gold-palladium core-shell nanorods - K Locharoenrat; P Damrongsak (My University, 2015)
We focus on the plasmonic properties of palladium-coated gold nanorods.Two characteristic plasmon bands of those nanorods have been detected in the optical absorption.One of them, which is located at about 525 nm, is associated with electron oscillations along the transverse direction.This band does not depend on the palladium-shell thickness and the dielectric susceptibility of the surrounding medium.The other band, at about 800-900 nm, is associated with electron oscillations along the longitudinal direction.It exhibits a clear shift when the palladium-shell thickness and the dielectric surrounding are changed.Our results point to a novel possible way for tuning photo-catalytic ability of the nanorods and their possible use in biological/chemical sensors.
Keywords: Nanorod; Gold and Silver Nanoparticles Synthesis and Applications